Estimating marginal value of water for irrigated olive grove with the production function method - Mesa-Jurado, M. A.; Berbel, J.; Orgaz, F. (Spanish Journal of Agricultural Research, 2010)
Economic valuation of irrigation water is done through the use of production functions for the case of the olive grove. In order to do so the integration of an agronomic model (based on the production function) and an economic model linked to the profitability of the crop (the ratio of revenue and operating costs) in the area under study is proposed. The study case encompasses the Guadalbullon River Sub-basin area, belonging to the Guadalquivir River Hydrologic Demarcation (Southern Spain). Within the overall deficit of the Guadalquivir River basin, the Guadalbullon River poses a special problem as it is unregulated and there are important irrigated fields on its banks, most of them olive groves. Net marginal value of water obtained (having deducted the variable costs of production including harvesting and irrigation) is€ 0.60 m–3 for the allocation of 1,000 m3 ha–1 and € 0.53 m–3 for the water right allowance of 1,500 m3 ha–1 (average for period 2005/2008). The results obtained support the recommendation by other authors suggesting the use of deficit irrigation in olive, additionally the high value of water estimated contributes to explain the substantial increase in irrigated olive area in Andalucia.